The impact of cultural aspects on sustainability in residential houses: Sulaymaniyah city as a case study - Mohammed, Kani; Ali, Alan Faraydoon (Edelweiss Applied Science and Technology, 2025)
This study aims to address the gap in the literature regarding the interplay between cultural identity and sustainable housing, particularly in Sulaymaniyah, a city in Iraq's Kurdistan region. The city, known for its rich traditional Kurdish architecture, has experienced rapid urbanization, leading to an increased demand for modern housing solutions. However, this shift toward modern housing has often compromised the preservation of the region's architectural heritage, prioritizing functionality and aesthetic appeal over cultural and environmental sustainability. This transformation threatens both the cultural integrity of the city and the efficient use of its natural resources. While the environmental impacts of contemporary housing have been well-researched, few studies have explicitly examined how cultural factors influence the sustainability of residential housing in Sulaymaniyah. Through mixed-method approach, including case studies, field observation, and questionnaires with architects and urban planners, this research investigates how traditional housing elements have adapted to contemporary influences. It aims to explore the role of cultural identity in sustainable design and to propose a hybrid approach that blends modern energy-efficient technologies with traditional architectural practices and materials. By highlighting the importance of integrating cultural values with sustainability efforts, this study provides valuable insights for policymakers, architects, and urban planners working to develop housing solutions that are both environmentally and culturally sustainable.